2016
DOI: 10.1002/jmri.25296
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of basilar artery atherosclerotic plaque distribution by 3D MR vessel wall imaging

Abstract: Taking advantage of 3D MR vessel wall imaging, BA plaques were found to more likely affect lateral walls and form in BA distal to AICA, where most perforators originate, suggesting that it might be useful to characterize BA plaque distribution before aggressive treatment for prevention of perforator stroke. J. Magn. Reson. Imaging 2016;44:1592-1599.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…In this study, most plaques were distributed eccentrically and predominantly located at the right, left and dorsal walls, where most of perforating arteries originate [26]. Chen et al [27] found that the most severe plaques of BA were commonly located at the left and right walls, which was similar to our results. Nevertheless, a previous study showed that the majority of middle cerebral artery plaques were located opposite to the orifice of perforating artery [28], different from our study.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, most plaques were distributed eccentrically and predominantly located at the right, left and dorsal walls, where most of perforating arteries originate [26]. Chen et al [27] found that the most severe plaques of BA were commonly located at the left and right walls, which was similar to our results. Nevertheless, a previous study showed that the majority of middle cerebral artery plaques were located opposite to the orifice of perforating artery [28], different from our study.…”
Section: Discussionsupporting
confidence: 90%
“…Larger ICAPs with diffuse distribution appeared to be a specific feature of posterior circulation lesions over those in the anterior circulation (74.3% in posterior, 31.8% in anterior circulation), which is consistent with the results of a previous study. 33 There are several limitations of the current study. First, all enrolled patients are Chinese, and therefore the results may not be applicable to other ethnicities.…”
Section: Discussionmentioning
confidence: 88%
“…Three-dimensional imaging methods (up to 0.5 mm isotropic) [44] can reduce the partial volume effect of 2D acquisition and allow the detection of non-stenotic basilar artery or PCA plaques. However, the long scan time and wider point spread function induced by long echo trains must also be considered [45, 46]. Another potential improvement is the use of automated segmentation.…”
Section: Limitationsmentioning
confidence: 99%